2009
DOI: 10.1016/j.mce.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 5 receptor activates ERK1/2 through a PI3K-regulated signaling mechanism

Abstract: receptor activates ERK1/2 through a PI3K-regulated signaling mechanism. Molecular and Cellular Endocrinology, Elsevier, 2009, 303 (1-2) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 31 publications
5
42
0
Order By: Relevance
“…The G s transduction pathway is established to be a validated path of signalling for all MCRs (Barrett et al 1994;Mountjoy et al 1992) all though other signalling pathways have been suggested (Buch et al 2009;Konda et al 1994;Daniels et al 2003;Rodrigues et al 2009). The natural occurring melanocortin peptide family consists of -, -and -melanocyte stimulating hormone (MSH) and adrenocorticotropic hormone (ACTH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The G s transduction pathway is established to be a validated path of signalling for all MCRs (Barrett et al 1994;Mountjoy et al 1992) all though other signalling pathways have been suggested (Buch et al 2009;Konda et al 1994;Daniels et al 2003;Rodrigues et al 2009). The natural occurring melanocortin peptide family consists of -, -and -melanocyte stimulating hormone (MSH) and adrenocorticotropic hormone (ACTH).…”
Section: Introductionmentioning
confidence: 99%
“…When a MCR is stimulated, it couples to G s , which activates intracellular adenylyl cyclase and increases cAMP production. -MSH stimulated phosphorylation of extracellular signal-regulated kinase (ERK) has previously been linked to lipolysis in 3T3-L1 cells and MC5R has been established to activate phosphatidylinositol 3-kinase dependent ERK after stimulation by -MSH (Rodrigues et al 2009). In addition, cAMP dependent AMPK has been linked to MC5R mediated fatty acid oxidation stimulated by -MSH in skeletal muscle .…”
mentioning
confidence: 99%
“…MC3R has been shown to induce inositol phosphate signaling (Konda et al, 1994) and MC5R was reported to activate the Janus kinase/signal transducer and activator of transcription (Jak/STAT) pathway in B cells (Buggy, 1998). Stimulation of all MCRs leads to activation of mitogen-activated protein kinases (MAPK) ERK-1/2 Chai et al, 2007;Herraiz et al, 2011;Patten et al, 2007, Rodrigues et al, 2009Roy et al, 2011). Depending on the cell type this effect may involve phosphoinositol 3 kinase activation (Rodrigues et al, 2009;Vongs et al, 2004).…”
Section: Mcr Signaling Pathwaysmentioning
confidence: 99%
“…Stimulation of all MCRs leads to activation of mitogen-activated protein kinases (MAPK) ERK-1/2 Chai et al, 2007;Herraiz et al, 2011;Patten et al, 2007, Rodrigues et al, 2009Roy et al, 2011). Depending on the cell type this effect may involve phosphoinositol 3 kinase activation (Rodrigues et al, 2009;Vongs et al, 2004). Some reports also show that ERK activation may be PKAindependent in MCR transfected cell lines Vongs et al, 2004).…”
Section: Mcr Signaling Pathwaysmentioning
confidence: 99%
“…It has emerged that many of the MCRs bind to endogenous peptides beyond the melanocortin peptides, which can act as agonists, antagonists, partial agonists, and even inverse agonists at these receptors (Cone, 2006). Furthermore, although the cAMP pathway continues to serve as the predominant readout of MCR function in many studies, numerous other intracellular signaling cascades for example the mitogen-activated protein kinase pathway have also been implicated in melanocortin signaling (Vongs et al, 2004;Sutton et al, 2005;Patten et al, 2007;Rodrigues et al, 2009). An additional feature of MCR signaling which has come to light over recent years is the presence of accessory proteins which regulate receptor function.…”
Section: The Melanocortin Systemmentioning
confidence: 99%